Assessment of Readiness Components for Attracting Medical Tourists in the Hospital Industry: A Survey Study in Western Iran - Zahra Shoara; Jamil Sadeghifar; Khalil Momeni; Mohammad Bazyar; Rahim Khodayari-Zarnaq; Maryam Heydari (Health Technology Assessment in Action)
Background: Efficient utilization of hospital beds is a key priority for healthcare systems today. Leveraging the potential of medical tourism can serve as a significant strategy in this regard. Objectives: The purpose of this study was to assess the readiness of hospitals in Ilam city to attract medical tourists. Methods: This descriptive cross-sectional study was conducted among educational and private hospitals in the center of Ilam province in 2023. Data were collected using a standard checklist designed to evaluate the International Patient Department (IPD), comprising 66 questions across five domains. The checklist was completed through observation, interviews, and a review of available documents. Data analysis was conducted using frequency and percentage distribution tables, means, and standard deviations in Excel software. Results: The highest readiness score for obtaining a license to establish an International Patient Department was achieved by Kowsar Private Hospital, with a score of 198. The lowest score was recorded at Razi Public Hospital, with a score of 119. Overall, none of the hospitals studied reached the cutoff score of 227 (65%). Conclusions: The results indicate that all the hospitals studied are currently in an unacceptable state of readiness to attract medical tourists. Establishing International Patient Departments should be a top priority for improving hospital efficiency and fostering the growth of medical tourism.